Anxiety and panic buying during COVID-19 pandemic among the Mizo - Ralte, Rinpari; Tipandjan, Arun; Halliday, Mary Ann L.; Zothanmawia, C.; Modi, Ritu; Nithiya, Devi R. (International Journal Of Community Medicine And Public Health, 2021)
Background: Certain behaviours have been observed since the beginning of the Covid-19 pandemic, such as buying and storing a lot of basic food and necessities, or hours spent obsessing over the virus. This research aims to assess the impact of the COVID-19 pandemic on the lives of the people living in Mizoram, a small north-eastern state in India, regarding psychological factors such as coronavirus anxiety and panic buying. Methods: A total of 300 samples aged 20-66 years (150 males and 150 females) participated in the online survey. Those who consented to participate filled the forms which included socio-demographic details, as well as the Corona Virus Anxiety Scale and the Panic Buying Scale. Results: Correlation analysis revealed significant positive correlations (r=0.21, p<0.000) between Coronavirus Anxiety and Panic Buying. Socio-demographic variables such as age (r=-0.12, p<0.05) and spirituality (r=0.13, p<0.05) are significantly correlated with panic buying, whereas number of family members was found to be significantly correlated (r=0.14, p<=0.05) with Coronavirus anxiety. Furthermore, females scored significantly higher than males in Coronavirus anxiety (p<0.002) and Panic Buying (p<0.007). Analysis also revealed that the number of hours spent in thinking about Covid-19 has a significant impact on Coronavirus Anxiety, and that growth in budget significantly influences Panic buying. Conclusions: One vital policy implication of the present study is that during a pandemic the government and other responsible organizations should ensure delivery of only factual data about COVID-19 and also reassure people about the adequacy of essential commodities so that panic buying is not rampant.